Circular RNA GLI2 promotes osteosarcoma cell proliferation, migration, and invasion by targeting miR-125b-5p - Ji-Feng Li; Yu-Ze Song (Tumor Biology)
Circular RNAs are novel identified type of endogenous non-coding RNAs, which exert vital functions in human and animals. However, the in-depth role of circular RNAs in the progression of tumorigenesis, especially osteosarcoma, is still undefined. Our preliminary study had found that cir-GLI2 was significantly upregulated in osteosarcoma tissues compared to adjacent non-tumor tissue. Moreover, cir-GLI2 silencing could effectively suppress the proliferation, migration, and invasion capacity of osteosarcoma cells, indicating the tumor-promoting role. Besides, bioinformatics analysis and luciferase reporter assay predicted the direct binding to miR-125b-5p, which has been reported to function as a tumor suppressor in osteosarcoma. Furthermore, functional experiments validated that cir-GLI2 exerted the tumor-promoting effects on osteosarcoma cells via negatively targeting miR-125b-5p. In conclusion, our study demonstrated that cir-GLI2 acts as an oncogenic circular RNA in osteosarcoma genesis, providing a novel diagnostic and therapeutic target for osteosarcoma.